Maternal Outcomes and Psychosocial Dilemma in sub-Saharan Africa: the case of Nigeria (2005)
Against the backdrop of persistent high maternal and infant morbidity and mortality, low acceptability of family planning programmes and increasing abortion rates, this paper observes that maternal outcomes in sub-Saharan Africa are events that depend on socio-cultural factors. The influence of male role, socio-economic status of women and access and use of health facilities on these outcomes are reinforced through the interplay of social - cultural beliefs and practices. A combination of these factors has led to psychosocial crises both at micro-individual and macro-society levels. To the extent that Talcott Parsons' Voluntary Social Action theory supposes that individuals are constrained, in their health seeking behaviour by culture, the present study argues strongly that re-definitions can be made in the face of obsolescence and manifest dysfunctionality of aspects of culture that are implicated in high maternal/infant morbidity and mortality and consequent psychosocial dilemma in sub-Saharan Africa. Recommendations affirm the essence of scaling up community responses and sensitization of key stakeholders to appreciate issues surrounding maternal events.